(3JYdjbI Ydi GdUMjaI GdSLGOjIs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO GdCUagGfj, J (B1111(3g` (B1700(3es ((3Rjf GdYGHOjf Hf eMeO WGgQs)
(3ChdgG (B:s
(3ChdgG(B: (3MOKfG GdSjO GdCLd (B... (3CHh GdMSf eMeO (B... (3bGd(B: (3dbjJ jMji Hf RjO Hf Ydj Ydjg GdSdGe hgh eJhLg Edi NQGSGf aSdeJ Ydjg abGd dj(B: (3ef Cjf GbHdJ?s
(3BNQgG (B:s
(3BNQgG(B: (3hCf JTQM HcJGHc UOQj hJMW HJdGhJg hRQj hJefMfj GdSdGeI aj Ojfj hfaSj hdG JhMT Hj Cgd CfSj hJJe EMSGfc ajeG Hbj ef YeQj ceG CMSfJ ajeG eVi efg jG CQMe GdQGMejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 48s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs